Seamless editing of the chloroplast genome in plants. Issue 1 (December 2016) - Martin Avila, Elena; Gisby, Martin; Day, Anil
Abstract Background Gene editing technologies enable the precise insertion of favourable mutations and performance enhancing trait genes into chromosomes whilst excluding all excess DNA from modified genomes. The technology gives rise to a new class of biotech crops which is likely to have widespread applications in agriculture. Despite progress in the nucleus, the seamless insertions of point mutations and non-selectable foreign genes into the organelle genomes of crops have not been described. The chloroplast genome is an attractive target to improve photosynthesis and crop performance. Current chloroplast genome engineering technologies for introducing point mutations into native chloroplast genes leave DNA scars, such as the target sites for recombination enzymes. Seamless editing methods to modify chloroplast genes need to address reversal of site-directed point mutations by template mediated repair with the vast excess of wild type chloroplast genomes that are present early in the transformation process. Results Using tobacco, we developed an efficient two-step method to edit a chloroplast gene by replacing the wild type sequence with a transient intermediate. This was resolved to the final edited gene by recombination between imperfect direct repeats. Six out of 11 transplastomic plants isolated contained the desired intermediate and at the second step this was resolved to the edited chloroplast gene in five of six plants tested. Maintenance of a single base deletion mutation in an imperfect direct repeat of the native chloroplastrbcL gene showed the limited influence of biased repair back to the wild type sequence. The deletion caused a frameshift, which replaced the five C-terminal amino acids of the Rubisco large subunit with 16 alternative residues resulting in a 30-fold reduction in its accumulation. We monitored the process in vivo by engineering an overlappinggusA gene downstream of the editedrbcL gene. Translational coupling between the overlappingrbcL andgusA genes resulted in relatively high GUS accumulation ( 0.5 % of leaf protein). Conclusions Editing chloroplast genomes using transient imperfect direct repeats provides an efficient method for introducing point mutations into chloroplast genes. Moreover, we describe the first synthetic operon allowing expression of a downstream overlapping gene by translational coupling in chloroplasts. Overlapping genes provide a new mechanism for co-ordinating the translation of foreign proteins in chloroplasts.